Liquidity effects on travel and tourism stocks following global financial crises - Gregoriou, Andros; Liasidou, Sotiroula (My University, 2019)
This paper explores liquidity effects following the global financial crises between 2007 and 2009 for 25 stocks listed on the Dow Jones Travel and Tourism Index. We find evidence of a sustained increase in the liquidity of the stocks as a result of the financial crises. The empirical findings are consistent with the information cost/liquidity hypothesis, which states that investors demand a lower premium for holding stocks with relatively more available information. Our results suggest that the travel and tourism industry is no longer considered a luxury item. On the contrary, it appears to be more of a necessity to stimulate business and happiness for firms and individuals, respectively, in times of financial turmoil.
Keywords: Liquidity; Financial Crises; Travel and Tourism; Dow Jones Travel and Tourism Index